2022
DOI: 10.5194/egusphere-2022-1401
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of S2S ensemble extreme precipitation forecasts over Europe

Abstract: Abstract. Heavy precipitation can lead to floods and landslides, resulting in widespread damage and significant casualties. Some of its impacts can be mitigated if reliable forecasts and warnings are available. Of particular interest is the subseasonal to seasonal (S2S) prediction timescale. The S2S prediction timescale has received increasing attention in the research community because of its importance for many sectors. However, very few forecast skill assessments of precipitation extremes in S2S forecast da… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Sub‐seasonal forecasts are more often represented as a week‐to‐week variation and are mostly evaluated on a weekly scale (Manrique‐Suñén et al., 2020; Rivoire et al., 2022; C. J. White et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Sub‐seasonal forecasts are more often represented as a week‐to‐week variation and are mostly evaluated on a weekly scale (Manrique‐Suñén et al., 2020; Rivoire et al., 2022; C. J. White et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…We also evaluate our model's capacity to detect extreme precipitation events. We define extreme precipitation as precipitation that exceeds the 90th percentile (Rivoire et al, 2023). We compute the empirical 90th percentile after excluding precipitation values below 1 mm.…”
Section: Assessment Of the Forecast Qualitymentioning
confidence: 99%
“…For extreme precipitation forecast, Olaniyan et al (2018) found that the S2S models could not reliably forecast the extreme precipitation during the West African monsoon. In addition, Rivoire et al (2023) assessed the forecast skill of the S2S extreme precipitation forecast and found high heterogeneity in the forecast skill over regions and seasons in Europe.…”
Section: Introductionmentioning
confidence: 99%